Development of an eco-friendly ultra-high performance concrete based on waste basalt powder for Sichuan-Tibet Railway. (20th August 2021) - Li, Yirui; Zeng, Xiaohui; Zhou, Junliang; Shi, Ye; Umar, Hussaini Abdullahi; Long, Guangcheng; Xie, Youjun
Abstract: Generally, tunnel waste is stacked in the slag field nearby for landfilling, which is harmful to sustainable development. The broken rocks and rock powder among the tunnel waste can be recycled to produce machine-made sand, producing many by-products calling rock powder. Based on the practical project, three types of waste basalt powder (BP), from tunnel excavation waste and by-products (rock powder) of machine-made sand producing from tunnel excavation waste in Sichuan-Tibet railway construction sites, was used to prepare an eco-friendly UHPC. The BP is used to replace the cement and is included in the design UHPC based on Modified Andreasen &Andersen particle packing model (MAA). Moreover, the chemical and physical behaviors and ecological evaluation of the designed UHPC and UHPC pasted were discussed. The results showed that when BP (Specific surface area 4.6582 m 2 /g) replaces up to 15%, the highest compressive strength of designed UHPC (220 MPa) was obtained. Compared with quartz powder, the pozzolanic activity of BP was generally low and increased with the increase of reaction temperature. However, the presence of BP and its fineness in UHPC pastes increased the values of the total autogenous shrinkage and decreased the total heat release at an early age of designed UHPC pastes, this effect is more pronounced with temperature increasing. Based on a quartering method with embodied carbon dioxide emissions and the compressive strength, UHPC with waste BP reduced embodied carbon dioxide and possessed higher compressive strength and lower environmental impact than the control samples of UHPC.